Analisis Pengaruh Organizational Citizenship Behaviour (OCB) Terhadap Kinerja Pegawai yang di Mediasi oleh Motivasi di PT. Permodalan Nasional Madani (PNM) Unit Galang - Sari, Vina; Batubara, Soulthan Saladin; Insan, Muhammad Yalzamul (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to examine the influence of Organizational Citizenship Behaviour (OCB) on employee performance mediated by motivation at PT Permodalan Nasional Madani (PNM) Galang Unit. This study uses a quantitative approach. Data was collected through questionnaires that were shared directly with respondents. Data analysis was carried out through the Partial Least Squares Structural Equation Modeling (SEM PLS) method. The results showed that OCB has a significant positive effect on employee performance, and motivation acts as a mediating variable that strengthens the relationship between OCB and performance. These findings indicate that increasing OCB can effectively improve employee performance if supported by high motivation. This research provides insight for company management to focus on developing OCB and motivation to improve employee performance